Assessment of Scientific Tools for Kinematic Analysis in Sports Performance - L, Ajithkumar; P, Kumar (Indonesian Journal of Sport, Health and Physical Education Science, 2025)
Kinematic analysis is crucial in sports science and biomechanics for optimizing performance and helping in rehabilitation. This study compares fifteen kinematic analysis tools, namely Siliconcoach, Kinovea, Templo by Contemplas, Gaiton, Helix 3D By Rundna, Dartfish, Coach’s Eye, Vicon, Motion Analysis Corporation, Noraxon Myoresearch, Qualisys, Pro-Trainer, Xsens, Simi Motion, And Shutter Precision. The comparison focuses on performance benchmarks, usability, accuracy, reliability, and cost-effectiveness. High-end systems like Vicon and Qualisys excel in precision and real-time data processing, ideal for research and professional use, while tools like Coach’s Eye offer accessible yet less precise analysis suitable for general coaching. Usability varies, with Kinovea and Dartfish noted for their user-friendly interfaces, while advanced systems require more extensive training. Accuracy is critical, with top systems providing high precision through sophisticated technologies. Cost varies widely, from free tools like Kinovea to premium systems like Vicon. This study provides valuable insights for selecting the most appropriate scientific tools and methods